Transforming higher education institutions through EDI leadership: A bibliometric exploration - Zhao, Xiangge; Wider, Walton; Jiang, Leilei; Muhammad Ashraf, Fauzi; Tanucan, Jem Cloyd M.; Lin, Jiaming; Udang, Lester Naces (Elsevier Ltd, 2024)
This comprehensive bibliometric study analyzes 1820 journal articles from the Web of Science database to explore Equity, Diversity, and Inclusion (EDI) leadership in higher education institutions (HEIs). Utilizing co-citation and co-word analysis, the study identifies distinct thematic clusters. The co-citation analysis reveals five key themes: Race, Diversity, and Inclusion (RDI), Diversity, Leadership, and Self-Efficacy (DLSE), Gender Dynamics and Leadership Challenges, Women's Representation in Academic Medicine Leadership, and Transformational Leadership in HEIs. Meanwhile, the co-word analysis highlights three critical areas: Transformative Collaborative Resilience in HEIs, Advancing Gender Equality in Academic Medicine and STEM, and Inclusive Educational Leadership in HEIs. These themes collectively provide a deep understanding of the EDI leadership field's intellectual structure, suggesting significant areas for future research and practical application. The study emphasizes the necessity for HEIs to engage comprehensively in EDI leadership research, shedding light on the importance of transformative collaborative resilience, gender equality in STEM, and inclusive leadership. This research offers valuable insights for developing effective EDI leadership policies and practices, highlighting the interconnectedness of these themes in fostering a more equitable, diverse, and inclusive environment in higher education and beyond.